Analysis of internal and external factors affecting agricultural productivity - Khatamov Ochildi Kurbanovich (THE INNOVATION ECONOMY, 2026)
The article classifies internal and external factors affecting agricultural productivity and studies their interrelationships. Also, the impact of these factors on agricultural production is assessed using statistical methods.